How to evaluate a syllabus for an online course. - David Line Denali; Mary-Katherine Smith; Stephen F Pyle (Academic Chairpersons Conference Proceedings, 2016)
This session explores how to determine strengths and weakness of an online course by examining the syllabus. Presenters and participants will move beyond the technical aspects such as alignment of content and into the flow of the online course. For this workshop participants are welcome to provide a syllabus for review.
Keywords: Online Course Layout Syllabus Review